2001
DOI: 10.1177/00912700122010050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety of Bone Remodeling Agents with a Focus on Osteoporosis Therapies

Abstract: This article reviews the different treatments currently available for osteoporosis and examines the benefits and adverse events that are associated with each. While emphasizing safety considerations, this review summarizes the following treatments for osteoporosis: calcium supplements, fluoride, hormone replacement therapy, raloxifene, bisphosphonates, salmon calcitonin, and calcitriol. Before prescribing any of these agents, the clinician should review the risk/benefit profile of each drug in the context of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…For example, tamoxifen and raloxifene are selective estrogen receptor modulators that work, at least in part, by antagonizing estrogen binding [1,2]. In addition to their use in the treatment of cancer, such estrogen receptor antagonists are beginning to be used for the treatment of cardiovascular diseases and osteoporosis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, tamoxifen and raloxifene are selective estrogen receptor modulators that work, at least in part, by antagonizing estrogen binding [1,2]. In addition to their use in the treatment of cancer, such estrogen receptor antagonists are beginning to be used for the treatment of cardiovascular diseases and osteoporosis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to fluoride in drinking water has been shown to be beneficial for oral and general health, [1][2][3][4][5] especially in relation to dental caries and osteoporosis. In a study carried out in 21 cities in four states in the US, Dean et al 1 showed that exposure to water containing about 1 ppm fluoride in drinking water reduced caries experience by 50%.…”
mentioning
confidence: 99%
“…Salmon calcitonin (sCT), a polypeptide hormone composed of 32 amino acids, is a potent inhibitor of osteoclastic resorption and is therapeutically efficacious when used in the treatments of metabolic bone-related diseases such as postmenopausal osteoporosis, Paget's disease, and hypercalcemia [Rodan and Martin, 2000;Kleerekoper and Schein, 2001]. Like other therapeutic peptides, sCT can only be administered by parenteral or nasal route because of its physicochemical instability, susceptibility to proteolysis, large molecular weight, and limited ability to traverse biological barriers [Wearley, 2001;Banga and Chien, 1988].…”
Section: Introductionmentioning
confidence: 99%